Noninvasive respiration movement sensor based on distributed Bragg reflector fiber laser with beat frequency interrogation - Wo, Jianghai (2014)
A distributed Bragg reflector fiber laser-based respiration movement monitoring system has been proposed and experimentally demonstrated. To fabricate the sensing element for respiration monitoring, a fixture that consists of a plastic plate, a section of elastic textile is employed to experience and transfer the belly expansion induced pressure onto the cross-section of the laser cavity. By tracing the change of the beat signal that generates between two polarization lasing modes, the information of the respiration movement can be extracted in real time. Experimental studies have demonstrated that the system is able to detect both respiration waveform and rate simultaneously. Moreover, the recorded results show that the different gestures as well as the physiology conditions can be distinguished by monitoring the amplitude and period change of the waveform. It is anticipated that the proposed fiber laser-based sensor would be highly suitable for respiratory monitoring.